(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
Sustainable management of irrigated lands under semi-hydromorphic conditions requires optimization of the meliorative regime to prevent soil degradation, secondary salinization, and inefficient water use. This study presents the results of a three-year field experiment conducted in the Pakhtakor district (Jizzakh region) aimed at improving irrigation efficiency and soil water–salt balance through laser land leveling and the replacement of traditional distribution furrows with portable polyethylene irrigation flumes (KSN-50). The experimental design included three replications under a pre-irrigation soil moisture regime maintained at 70–70–60% of field moisture capacity (FMC), compared with conventional furrow irrigation. Irrigation scheduling was determined using gravimetric soil moisture analysis and tensiometer monitoring at 30, 50, and 70 cm depths. General and partial water–salt balances were calculated according to established hydromeliorative methodologies. The findings confirm that integrating precision land leveling with portable irrigation flumes significantly improves the meliorative regime, increases water-use efficiency, and ensures sustainable cotton production under irrigated conditions.